HIGHER-ORDER THINKING SKILL (HOTS) ANALYSIS OF GRADE IX STUDENTS ON BIOTECHNOLOGY MATERIALS - Fivty Octavia Astuti; Aa Juhanda; S Suhendar (Jurnal Pelita Pendidikan, 2021)
Higher Order Thinking Skills (HOTS) are substantial abilities that students must have as a basis for complex thinking skills. This study aims to determine the Higher Order Thinking Skills (HOTS) of eighth-grade students on biotechnology material. The research method used is qualitative. The population in this study were students at one of the boarding schools in the Sukabumi district. The research sample consisted of 24 students. The instrument used was multiple-choice test questions with four choice options. The questions used in this study have a reliability of 0.7 (sufficient) and validity of 0.8 (high). The research data showed that the students 'HOTS ability was still low. The t-test results, which compared the students' acquisition scores with the completeness score (60), obtained a sig value of 0.78, meaning that there was no difference in the mastery score and the HOTS acquisition of students. Calculation data based on cognitive level categories, learning indicators, and achievement categories also show that the HOTS ability of students is still low